Concomitant Langerhans cell histiocytosis of cervical lymph nodes in adult patients with papillary thyroid carcinoma: A report of two cases and review of the literature - Bayan Maraqa; Maxim Al-Ashhab; Nazmi Kamal; Mousa El Khaldi; Maher Sughayer (University of São Paulo, 2021)
Objective: Langerhans cell histiocytosis (LCH) is an uncommon entity of unknown etiology. It contains a wide range of clinical presentations. The discovery of oncogenic BRAF V600E mutation in LCH has provided additional evidence that LCH is a neoplasm. Papillary thyroid carcinoma is the most common cancer of the thyroid characterized by a high incidence of BRAF V600E mutations. LCH with concomitant PTC is rare, with few cases reported in the literature. Cases summary: We identified two cases of LCH with concomitant papillary thyroid carcinoma in adult patients. The first was a 49-year-old female with a thyroid nodule diagnosed with papillary thyroid carcinoma. Later, the patient had a left neck mass; Ultrasound-guided lymph node FNA was diagnosed with Langerhans histiocytosis. Subsequently, a chest CT scan revealed signs of Langerhans cell histiocytosis in the lung. The second case refers to a 69-year-old male who presented with a left thyroid nodule diagnosed on FNA cytology as papillary thyroid carcinoma. The patient was found to have multiple bone lytic lesions. Biopsies revealed Langerhans cell histiocytosis. Later, the patient experienced LCH involvement of the bone marrow with associated secondary myelofibrosis. Conclusions: LCH is rare in adults; the association with papillary thyroid carcinoma is reported and should be considered in the presence of Langerhans cell groups along with PTC, whether in the thyroid gland or cervical lymph nodes. Once LCH has been diagnosed, pulmonary involvement should also be investigated. This will direct treatment plans for patients with pulmonary or systemic disease involvement.